Feline infectious peritonitis: two clinical cases in Lima, Peru - Rubio V., Alicia (2018)
Feline Infectious Peritonitis (PIF) is a lethal disease in cats caused by a coronavirus, which until now has no curative treatment. Two clinical cases are described: a 6-month Siamese male with apathy and anorexia and a 19-month female with short hair who was presented with abortion and decay. Both patients presented mild to severe ascites with a yellowish and protein peritoneal fluid compatible with wet form of PIF. At necropsy ascites was found and fibrin gelatinoid masses adhered to the serosa of liver, spleen, pericardium, intestine and mesentery were observed in both patients. Histopathology showed copious mixed inflammatory exudate composed of fibrin strings interspersed with neutrophils at varying degrees of degeneration and plasma cells, accompanied by severe vasculitis with cytoplasmic swelling of endothelial cells and effusion of acidophilic proteinic fluid.